Integrated management improves emerging coastal industries and ecological restoration with the participation of social capital - Shusheng, Xu; Jingqian, Xie; Mianrun, Chen (Frontiers in Marine Science, 2023)
In order to give policy advices to support continuous ecological restoration and coastal economy development, in this paper, we found insufficient funds and insufficient space are the main problems of mangrove restoration projects in China and Southeast Asia countries, The average cost of mangrove restoration projects in China was calculated, the result shows it was about RMB 999,000/ ha, and the mangrove restoration funding gap will be RMB 1,500,000,000 per year. The advantages and problems of coastal emerging industries was analyzed, the result shows that the common problem of emerging industries is insufficient space, some of them are lack of subsidies. Learning from the enlightenment of inland areas and Southeast Asian countries, we proposed a plan of integrated management improves both emerging marine industries and ecological restoration with participation of social capital, we also designed the time roadmap of the plan based on target area A. In order to validate this plan, the strengths, weaknesses, opportunities and threats (SWOT) of the plan were analyzed. The SWOT analysis showed that the plan is a win-win model plan, which can generally meet the local governments needs such as ecological restoration, pollution control, industrial upgrading and residents' income improvement. At last, we suggest that governments should strengthen cross department coordination, improve current sea area use policies and strengthen publicity.